Anatomical Feasibility Study on Novel Ascending Aortic Endograft With More Proximal Landing Zone for Treatment of Type A Aortic Dissection - Li, Xiaoye; Zhu, Longtu; Zhang, Lei; Song, Chao; Zhang, Hao; Xia, Shibo; Guo, Wenying; Jing, Zaiping; Lu, Qingsheng (Frontiers in Cardiovascular Medicine, 2022)
Objective Type A aortic dissection (TAAD) is associated with high morbidity and mortality, and open surgery is the best treatment option. Development of endovascular repair devices for TAAD will benefit patients deemed unfit for open surgery. In this study, we performed a thorough investigation of anatomical features in Asian patients with TAAD to learn about the patient eligibility of a novel ascending aortic endograft technique. Methods Computed tomography angiography (CTA) images of TAAD cases in our institution from January 2015 to November 2021 were reviewed, and three-dimensional reconstructions were performed with the Endosize software (Therenva, Rennes, France). Anatomic structures including length measured along centerline and greater/lesser curvature, ascending aorta/aortic root dimensions, as well as location of entry tear and extent of dissection were analyzed. Results A total of 158 patients were included [median age 58 years, interquartile range (IQR), 30–76 years; 115 males, 72.8%]. In 99 (62.7%) of the cases, entry tear was distal to the sinotubular junction (STJ). In 106 (67.1%) of the cases, the pathology proximally extended into the aortic root, which was intramural hematoma in 37 (23.4%) of the cases, and the aortic root was free from the pathology in 52 (32.9%) of the cases. The median distance from the STJ to the proximal edge of the ostium of the innominate artery (IA) measured along the centerline was 65 mm (IQR 58–74 mm). The median distance from the distal edge of the higher coronary ostium to the STJ was 7.95 mm (IQR 5.625–10.9 mm). The bare metal stent part was set between the edge of the higher coronary ostium and the STJ. In our series, 63 (39.9%) of the cases had this distance >10 mm. The relative difference was <20% between the STJ and the proximal edge of the ostium of the IA in 92 (58.2%) of the cases. Ascending aorta radius of curvature was 52.2 mm (IQR 43.7–63.7 mm). Conclusions Our study demonstrates that 56.3% of the TAAD cases would be amenable to endovascular repair by the novel ascending aortic endograft, with sufficient landing zone free of the dissected aorta.